2020
DOI: 10.3390/w12051311
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Ecological Response of Planktic and Benthic Epipelic Algae to Environmental Factors in an Urban Rivers System

Abstract: Many studies have been concentrated on the distribution of algae in lakes, rivers, and seas, however, few studies have been concerned about their distribution and relation with polluted urban rivers. In this study, the spatio-temporal variation characteristics of water quality and algae community in Nanjing city were investigated with microscopic examination for one year. Results showed that the water pollution in this area was mainly related to high concentration of nitrogen (NH3-N and TN (Total nitrogen). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Changes in vegetation cover have been shown to influence algal community [9]. The abundance of diatoms is an indication of high nutrient status of the sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in vegetation cover have been shown to influence algal community [9]. The abundance of diatoms is an indication of high nutrient status of the sites.…”
Section: Discussionmentioning
confidence: 99%
“…Algae have responded to variations in water chemistry, season, and physiography variables [8]. Studies conducted in tropical and subtropical Africa indicated that the community assemblages of diatoms were impacted by human induced water quality alterations [5] [9] [10] [11] [12]. Being microscopic, they are the first to sense and respond to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al [5] showed that although eutrophication is a key stressor for algae, planktonic and epipelic algae are affected differently by nutrients. Temperature, TP, and TN can be regarded as main stressors for planktonic algae, whereas TN and N:P ratios are more critical for epipelic algae.…”
mentioning
confidence: 99%